A Shadow Dynamic Finite State Machine for Branch Prediction: An Alternative for the 2-bit Saturating Counter (Informatica, 2025)
A Shadow Dynamic Finite State Machine for Branch Prediction: An Alternative for the 2-bit Saturating Counter